Cervical Interferential Current Transcutaneous Electrical Sensory Stimulation for Patients with Dysphagia and Dementia in Nursing Homes - Hara, Yoshiko (Clin Interv Aging, 2021)
PURPOSE: We aimed to determine the efficacy of interferential current transcutaneous electrical sensory stimulation (IFC-TESS) in patients with dementia who were being treated for dysphagia in nursing homes under normal living conditions. PATIENTS AND METHODS: This study recruited 54 nursing home residents (13 males, 41 females; mean age, 84.5 ± 10.7 years) with dysphagia and dementia. IFC-TESS was performed with Gentle Stim(®) (Careido Co. Ltd., Kanagawa, Japan) for 15 minutes. Two sessions per day were administered 5 days per week, for 3 weeks. The outcomes included the improvement of the patients’ cough reflexes and nutritional states across the 3 weeks of intervention; the former was evaluated with the cough test based on the changes in cough latency time and cough frequency, while the latter was assessed based on changes in the functional oral intake scale (FOIS) score and oral calorie intake. RESULTS: The cough latency times before and after the 3-week intervention were 15.8 (7.0–60.0) and 6.7 (3.6–30.7) s/min, respectively; the cough frequencies were 5.0 (0.0–5.0) and 5.0 (5.0–5.0) t/min, respectively; the FOIS scores were 5.0 (5.0–6.0) and 5.0 (5.0–6.0), respectively; and oral calorie intakes were 1300.0 (862.5–1420.0) and 1300.0 (1005.0–1462.5) kcal/day, respectively. All parameters significantly improved across the intervention (p < 0.05). When the results were adjusted for age, sex, body mass index, mini nutritional assessment results, Barthel index, and mini-mental state examination scores, IFC-TESS improved the cough reflex and oral calorie intake in older nursing home residents with dementia. CONCLUSION: Cervical IFC-TESS can improve the cough reflexes and nutritional states of patients with dysphagia and dementia in nursing homes. As it has previously been difficult to perform active rehabilitation with dementia patients, IFC-TESS may be effective and practicable for the rehabilitation of this patient population.